Network pharmacology uncovers that secoisolariciresinol diglucoside ameliorate premature ovarian insufficiency via PI3K/Akt pathway - Zhang, Yiqing; Liu, Xialu; Zheng, Zitong; Huang, Haiqiang; Wang, Yurou; Wu, Shuqin; Shu, Yuan; Yang, Yuxin; Zhong, Yufei; Liao, Pengfei; Wang, Yongsong; Pan, Zezheng (Scientific reports, 2025)
As one of the essential lignan derivative found in traditional Chinese medicinal herbs, secoisolariciresinol diglucoside (SDG) was proved to promote women’s health through its phytoestrogenic properties. Increasingly studies indicated that this compound could be a potential drug capable of preventing estrogen-related diseases. Here, we aimed to investigate whether SDG can counteract cyclophosphamide (CTX) induced premature ovarian insufficiency (POI) and further explore its specific molecular mechanism. In this study, we first validated the therapeutic effect of SDG on POI in a mouse model. Then, the mechanism by which SDG improves POI is predicted through a combination of network and pharmacology, and its authenticity is further confirmed by experimental verification, molecular docking analysis and molecular dynamics simulation. The results showed that SDG significantly alleviated POI by improving ovarian indices and follicle counts while protecting against CTX-induced ovarian damage by modulating the PI3K/Akt signaling pathway in KGN cells. In addition, molecular docking studies confirmed SDG’s high affinity for Akt1 and PI3Kγ, pinpointing the precise interaction sites. These results underscore the protective mechanisms of SDG against ovarian damage, highlighting its therapeutic potential. In summary, our study identified that SDG can ameliorate CTX-induced POI with its mechanism of action intricately linked to the modulation of the PI3K/Akt signaling pathway.